The assembly of dialkyldimethylammonium bromide cationic lipids as vesicles or monolayers in presence of poly(ethylene glycol) - Adati, Renata D. [UNESP]; Feitosa, Eloi [UNESP] (Elsevier B.V., 2015)
The interaction between polymer and lipid vesicles may result in stabilization and formation of highly ordered networks, which can mimic biological membranes and be used as drug delivery system. Here we used differential scanning calorimetry (DSC) and Langmuir-Blodgett (LB) techniques to describe the effect of the nonionic water-soluble poly(ethylene glycol), PEG 35 kDa, on vesicles or monolayers from the cationic dialkyldimethylammonium bromide, D(n)DAB (n = 12-18). Based on DSC data, up to 10 Wt%, PEG plays minor role on the thermal behavior of D(n)DAB, thus preserving the bilayer structure. Above 10 wt% PEG, there is no bilayer for n = 12-16, while for n = 18 there remains bilayer structures even in presence of 30 wt% PEG. The effect of PEG on the Langmuir monolayer of D(18)DAB depends on the amount of PEG in the sub-phase. In presence of up to ca 1 wt%, PEG yields more compressible films, while at higher polymer concentration the film is more extended and the collapse pressure is lower, most probably due to lipid solubility by the polymer solution. The PEG-D,DAB complexes have potential application in controlled drug release by microgel nanoparticles. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Differential scanning calorimetry; Dialkyldimethylammonium bromide salts; Poly(ethylene glycol); Langmuir films; Polymer-surfactant interaction